A simultaneous assessment of the hierarchical models of market orientation and External Environmental Factors (EEFs) on the relationship between innovation orientation and concept development in chain restaurants / Mazalan Mifli - Mifli, Mazalan (Institute of Graduate Studies, UiTM, 2015)
This thesis is about extending the research on menu innovation process in chain restaurant industry. The global consumer foodservice markets, nowadays, are mostly at the stage of saturation, and this presents great challenges to the industry. Hence, a viable new model of menu innovation process has been long sought in hospitality literature. Yet, models of menu innovation process proposed in literature are mostly conceptual in nature rather than empirically derived. Thus, this poses a question of the viability of its usage given the fact that most business landscapes, if not all, are not homogenous. Furthermore, most companies, if not all, are also governed in difference managerial orientations that dictate the directional of the product development process based on the preference towards risk-taking, entrepreneurship, objectivity, assertiveness and information use. Because of this, external environmental factors that build up in the marketplace are, therefore, to be conceived differently by menu planners, which subsequently, dictate a new strategy in managing new menu innovation. Hence, this thesis aimed to empirically investigate the actual practice of managing menu innovation in the chain restaurants that are operating in the consumer market of Klang Valley in Malaysia. The objective is to empirically examine the two orientations that are commonly associated with product innovation that include radical and incremental product development. Specifically, to simultaneously assess the moderating effect of the external environmental factors (EEFs) along with the mediating effect of market orientation on the relationship between innovation orientation and concept development. The empirical setting of chain restaurant is chosen because they are known to be strategically better equipped in managing product innovation in terms of consistency, speed, standardise quality and adaptation as opposed to independent restaurants…